Catalyzing aid? The IMF and donor behavior in aid allocation - Stubbs, T; Kentikelenis, A; King, L (Elsevier, 2015)
The International Monetary Fund (IMF) has often asserted that its programs encourage aid by signaling policy credibility, commonly referred to as aid catalysis. Our study investigates this claim for sector-specific aid and for bilateral and multilateral donors using data on 136 recipient countries for the 1986–2009 period. We employ a two-part quantitative model to match the donor decision-making process, consisting of a first-stage recipient selection equation and a second-stage allocation equation on selected recipients. We find strong support that IMF programs catalyze aid on aggregate, but the evidence varies across different types of aid. Aid catalysis is stronger and more robust in sectors linked to the IMF’s core competency areas, namely debt-related relief and general budget support, but weaker and less robust for infrastructure, production, multisector, and humanitarian aid, and non-existent for health and education. Across donors, IMF programs are associated with increases in aid by countries with larger voting shares in the IMF, such as the United States and Japan, but less so by countries with few votes or for multilateral agencies. This finding is consistent with research in international political economy arguing that the IMF’s powerful stakeholders drive the organization’s decisions and policies. Taken together, our findings emphasize the IMF’s multi-dimensional impact on the global development agenda—an erstwhile overlooked factor in studies of aid allocation—while refuting the purported positive effects of IMF programs on aid for social policy.